Dietary sodium enhances the expression of SLC4 family transporters, IRBIT, L-IRBIT, and PP1 in rat kidney: Insights into the molecular mechanism for renal sodium handling - Cai, Lu; Wang, Dengke; Gui, Tianxiang; Wang, Xiaoyu; Zhao, Lingyu; Boron, Walter F.; Chen, Li-Ming; Liu, Ying (Frontiers in Physiology, 2023)
The kidney plays a central role in maintaining the fluid and electrolyte homeostasis in the body. Bicarbonate transporters NBCn1, NBCn2, and AE2 are expressed at the basolateral membrane of the medullary thick ascending limb (mTAL). In a previous study, NBCn1, NBCn2, and AE2 are proposed to play as a regulatory pathway to decrease NaCl reabsorption in the mTAL under high salt condition. When heterologously expressed, the activity of these transporters could be stimulated by the InsP3R binding protein released with inositol 1,4,5-trisphosphate (IRBIT), L-IRBIT (collectively the IRBITs), or protein phosphatase PP1. In the present study, we characterized by immunofluorescence the expression and localization of the IRBITs, and PP1 in rat kidney. Our data showed that the IRBITs were predominantly expressed from the mTAL through the distal renal tubules. PP1 was predominantly expressed in the TAL, but is also present in high abundance from the distal convoluted tubule through the medullary collecting duct. Western blotting analyses showed that the abundances of NBCn1, NBCn2, and AE2 as well as the IRBITs and PP1 were greatly upregulated in rat kidney by dietary sodium. Co-immunoprecipitation study provided the evidence for protein interaction between NBCn1 and L-IRBIT in rat kidney. Taken together, our data suggest that the IRBITs and PP1 play an important role in sodium handling in the kidney. We propose that the IRBITs and PP1 stimulates NBCn1, NBCn2, and AE2 in the basolateral mTAL to inhibit sodium reabsorption under high sodium condition. Our study provides important insights into understanding the molecular mechanism for the regulation of sodium homeostasis in the body.